Influencia de los roles de género en la práctica de los derechos sexuales y reproductivos de las estudiantes de IV ciclo de la Escuela Profesional de Trabajo Social de la Universidad Nacional de Trujillo, 2021 - Terrones Garcia, Fiorella Alessandra (2023)
The present thesis was carried out to analyze the influence of gender roles in the practice of sexual and reproductive rights of the fourth-cycle female students of the University of Trujillo Social Work Professional School. Therefore, the research's specific objectives are identifying the gender roles assimilated by the female students and describing their influence in the exercise of students' sexual and reproductive rights. In order to do this, the research had used a sample of 58 female students and applied inductive-deductive, analytical–synthetic, and statistical methods. In addition, the techniques employed were the interview, the survey, and the bibliographic review. The research instruments were the interview guide and record, the questionnaire, and the documentary sources. These instruments were utilized to obtain the quantitative and qualitative data to analyze the research variables. After the analysis, it was concluded that gender roles do have a direct and negative influence on the exercise of sexual and reproductive rights of the fourth-cycle female students of Social Work Professional School. This can be identified in their differentiated perception of the exercise of sexuality by men and women. Also, it can be show in the self-determination of students about their sexual and reproductive.